(untitled) (Journal of International Studies, 2025)
Since 1949, The People’s Republic of China has pursued the overarching objective of “reunifying” Taiwan, with its policies and practices consistently grounded in the principle of “One China.” Over time, Beijing’s approach has undergone a notable transformation, shifting from coercive strategies toward the framework of “One Country, Two Systems,” a change that reflects broader geopolitical shifts in the post–Cold War era as well as the United States’ commitment to Taiwan’s security. More recently, Taiwan’s Democratic Progressive Party (DPP) leadership has articulated positions such as “Taiwan is already a sovereign state” and “the mainland and Taiwan are mutually independent.” These assertions have heightened Beijing’s concerns, leading to statements that it “will not renounce the use of force if necessary” and to the staging of large-scale military exercises around the island, significantly intensifying regional tensions. This study examines the historical evolution and current trajectory of cross-Strait relations, examining the shifting policies of mainland China toward Taiwan. Particular attention is given to the theoretical underpinnings, mechanisms, and implementation of Beijing’s strategy of “peaceful reunification,” as well as to Taiwan’s responses within the context of domestic political dynamics and external influences. Taiwan’s countermeasures and strategies to resist pressure from the mainland will be the subject of a subsequent study. БНХАУ-аас Тайваньд хэрэгжүүлж буй бодлого, үйл ажиллагаа Хураангуй: Хураангуй: БНХАУ-аас Тайваньд хэрэгжүүлж буй бодлого, үйл ажиллагаа нь “Тайванийг өөртөө нэгтгэх” зорилтын дор 1949 оноос хойш тасралтгүй үргэлжилж байна. Хятадаас Тайваньд чиглэсэн бодлого, үйл ажиллагаа нь түүний эрх баригчдын дэвшүүлсэн “Нэг Хятад” бодлогод суурилж, аажмаар энэ нь “Нэг Хятад, Хоёр Систем”-ийн бодлого буюу “хатуу”-гаас “зөөлөн” арга хэлбэрт шилжих замаар дүр төрхөө өөрчилжээ. Энэ нь “Хүйтэн дайн”-ы дараах геополитикийн нөхцөл байдалд гарсан өөрчлөлт, Тайванийг хамгаалах АНУ-ын амлалт зэрэгтэй уялдсан бодлогын томоохон шилжилт юм. Гэвч сүүлийн жилүүдэд Тайванийн Ардчилсан дэвшилт намын эрх баригчид “Тайвань аль хэдийн тусгаар тогтносон улс”, “Эх газар, Тайвань хоёр нь харилцан хамааралгүй” зэрэг байр суурь илэрхийлэх болсон нь Хятадын эрх баригчдыг түгшээн, “шаардлагатай тохиолдолд цэргийн хүч хэрэглэхээ буцахгүй” хэмээн мэдэгдэж, Тайвань арлыг тойрсон томоохон цэргийн сургуулилт явуулах болсон нь бүс нутгийн нөхцөл байдлыг хурцатгаж байна. Иймд энэхүү судалгаагаар, “Хоёр эрэг”-ийн харилцааны түүх, одоохи нөхцөл байдал, Эх газраас Тайваньд хэрэгжүүлж буй бодлогын өөрчлөлт, ялангуяа түүний “Тайванийг энх тайвнаар нэгтгэх” үйл ажиллагааны онолын үндэслэл, хэрэгжүүлж буй арга хэлбэр, Тайванийн хариу үйлдэл, тэдгээрт нөлөөлөх дотоод, гадаад хүчин зүйлийг авч үзэв. Түлхүүр үгс: “Хоёр эрэг”, “Эх газар”, Тайвань, “Нэг Хятад, Хоёр систем”, “92 оны зөвшилцөл”, “Дайны 3 номлол”